Observations of acyl peroxy nitrates during the Front Range air pollution and photochemistry éxperiment (FRAPPÉ) - Zaragoza, Jake, author; Fischer, Emily V., advisor; Collett, Jeffrey L., committee member; Farmer, Delphine, committee member (Colorado State University. Libraries, 2016)
The Colorado Front Range is an ozone (O3) nonattainment region. The photochemistry of the region is influenced by emissions from the urban and oil and gas sectors, the complex terrain, and the meteorology. The Front Range Air Pollution and Photochemistry Éxperiment (FRAPPÉ) was a field intensive carried out in the Colorado Front Range during summer 2014 to characterize the regional chemical environment. Acyl peroxy nitrates (PANs) play important roles in atmospheric chemistry, acting as either sinks or sources for nitrogen oxides (NOx) depending on conditions. PANs and other trace gas species were measured at the Boulder Atmospheric Observatory (BAO) during FRAPPÉ. Situated at the southwestern edge of the Denver-Julesburg Basin and 35 km north of Denver, BAO has been the site of multiple field studies aiming to characterize the influence of emissions from the oil and gas sector. Here we focus on an analysis of the PANs measurements from BAO during FRAPPÉ. In particular, we focus on peroxyacetic nitric anhydride (PAN, CH3C(O)O2NO2), peroxymethacrylic nitric anhydride (MPAN, CH2C(CH3)C(O)O2NO2) and peroxypropionic nitric anhydride (PPN, CH3CH2C(O)O2NO2). Mean and maximum PAN mixing ratios (5-minute point) were 275 and 1519 pptv respectively. There were four days during FRAPPÉ where the observed PAN abundance exceeded 1 ppbv. These days were examined using FLEXible PARTicle dispersion model (FLEXPART) back trajectories in order to determine air mass origin. The high PAN days occurred when air masses were recirculating in the region, often under Denver Cyclones. However, a visual inspection of FLEXPART trajectories throughout FRAPPÉ showed that recirculation events in the region occurred on days with high (>1 ppbv), moderate (500 pptv − 1 ppbv), and low (<500 pptv) afternoon PAN mixing ratios. The PPN/PAN ratio observed at the BAO tower during the summer of 2014 was 21%, which suggests anthropogenically enhanced photochemical activity. The ratio was very consistent (R2 = 92%) and not dependent on wind direction, potentially reflecting a lack of variability in regional non-methane volatile organic compound (NMVOC) chemistry. The MPAN/PAN ratio was <5%, indicating that isoprene oxidation had very little influence on photochemistry compared to many other regions in the U.S. The relative abundances of PPN and MPAN were used to estimate the contribution of isoprene oxidation to local O3 production. It was found that the contribution to local O3 from isoprene oxidation was consistently less than 20%. The findings of this study suggest that anthropogenic emissions are the key drivers of PANs and O3 formation in the region.